History of computer display and technology on PC / Ahmad Sabri Abdul Rashid - Abdul Rashid, Ahmad Sabri (2000)
This study discusses about history of computer display and technology used on personal computer (PC) only. The main study area is gathered systematically started from the day of monochrome is invented until flat panel displays technology including a little bit about gas plasma. After delving deep into what is computer display subject matter, it is found out that computer display goes hand in hand with 4 other subjects: monitor, display system, display adapters and displays. Every subject has related with one another. To know computer display, definitely must know what is monitor, display system, display adapters and displays. This study also proposed a web base application which can used to present all the information about the history of computer display and technology used on PC in more efficient and effective.